Parameter-elliptic operators on the extended Sobolev scale - Zinchenko, T.; Murach, A. A. (Methods of Functional Analysis and Topology, 2013)
Parameter–elliptic pseudodifferential operators given on a closed smooth manifold are investigated on the extended Sobolev scale. This scale consists of all Hilbert spaces that are interpolation spaces with respect to a Hilbert–Sobolev scale. We prove that these operators set isomorphisms between appropriate spaces of the scale provided the absolute value of the parameter is large enough. For solutions to the corresponding parameter–elliptic equations, we establish two-sided a priori estimates, in which the constants are independent of the parameter.